Effect of Alkaline Diet with 8-week Step Aerobic Exercise on Body Composition and Aerobic Exercise Performance of Sedentary Women - Yalcinkaya, Nehir; Cetin, Onat; Beyleroglu, Malik; Isik, Ozkan; Eker, Salih; Bilge, Murat (Progress in Nutrition, 2020)
Study Objectives: The aim of this study was to investigate the effect of an alkaline diet with step aerobic exercises for 8-week in sedentary women on their body composition and aerobic exercise performances. Methods: 22 sedentary women (age = 49.18 ± 6.28) voluntarily participated in the study (n = 11 alkaline diet group; n = 11 acidic diet group). Alkaline diet and acidic diet programs were applied to the sedentary women together with step aerobic exercises for 8 weeks. This research was designed as a randomized controlled trial model. Body composition (total body weight, fat mass, and free-fat mass), aerobic exercise performance indicators (Bruce treadmill test, lactate accumulation, estimated VO2Max, and rating of perceived exertion) were measured before and after diet and exercise programs. Results: The results of the body weight, fat mass, lactate accumulation, and rating of perceived exertion levels of the group consuming an alkaline diet together with the eight-week step aerobic exercises showed a higher decrease and aerobic exercise performance duration and VO2Max levels indicated a higher increase than acidic diet group. Conclusion: The alkaline diet with reduced acid value together with 8-week step aerobic exercises in sedentary women, has a high rate of positive effects on body composition and aerobic exercise performances.